Organic acids concentration in citrus juice from conventional versus organic farming - Duarte, Amílcar (2013)
Every day consumers make choices about what to eat and ask themselves “Should I be buying organic food?” For producers, is very important to have technical information about the quality of organic products. It can facilitate to demonstrate the quality of organic products, in comparison with conventional ones. The purpose of our work was to compare internal and external characteristics of citrus, produced in organic versus conventional farming. The study was carried out in the south of Portugal. Fruits of different orchards have been harvested and submitted to physical and chemical analyses, as well as to a sensorial test. The analyses showed that the farming system affected fruit quality. Special attention was paid to the concentration of vitamin C, a compound which plays an important role in human health. Fruits from organic farming had a higher level of vitamin C, compared with fruits from conventional production. However, this result was not obtained in all cultivars. The concentration of other organic acids was also evaluated. Results showed clear differences between cultivars and between the two farming systems. In most cases, concentration of organic acids was higher in the citrus fruits from organic farming.